SUKUURU KAASUTO YANG TERCERMIN DALAM MANGA PIKA ICHI KARYA MAKI YOUKO DAN MOCHIDA AKI - Restiati Ina Wea, Novita (Humanis, 2016)
The purpose of this research is to determine the structure, causes, and effects of the sukuuru kaasuto in manga Pika Ichi created by Maki Youko and Mochida Aki. The analysis showed that the structure of sukuuru kaasuto is divided into three levels, namely: team 1 or cool people; team 2 or ordinary people; and team 3 or disgusting people. The cause of the sukuuru kaasuto are: 1) the existence of strong orientation group in students; 2) students belief vertical relationships structure in the group; 3) teacher difference action to students; and 4) parents difference action to children. The effect of the sukuuru kaasuto are: 1) pressure felt by students; and 2) rebellion caused by members of team 3 to change their style.
Keywords: sukuuru kaasuto, group orientation, shuudan gang.